Profit Analysis of the Banana Chips Home Industry in Unaaha City - Sarty Syarbiah; Tauwi Tauwi (Green Economics: International Journal of Islamic and Economic Education, 2026)
This study aims to analyze the profit of the banana chips home industry "Sukses Abadi Snack" owned by Mrs. Suyamiati in Unaaha City. The respondent was purposively selected, focusing on the owner of the business. Data were analyzed using the profit analysis method to assess the financial performance of the business. The results indicated that the total cost of the business amounted to Rp. 5,864,025 per month. The breakdown of costs included fixed costs of Rp. 76,025 per month and variable costs of Rp. 5,788,000 per month. The total income generated by the banana chips business was Rp. 13,392,000 per month. The profit was determined by subtracting the total costs from the income. The net profit earned by the "Sukses Abadi Snack" home industry in producing banana chips reached Rp. 7,604,000 per month. This shows that the banana chips business is profitable and generates a substantial monthly profit for the owner.